2005
DOI: 10.1002/clc.4960280110
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker infection due to Aspergillus: report of two cases and literature review

Abstract: SummaryBackground: Aspergillus infections of pacing systems are extremely uncommon, and most cases reported are characterized by an aggressive behavior that may lead to death of the patient.Hypothesis: The study was undertaken to assess the incidence of pacemaker infection due to Aspergillus in a defined population.Methods: A retrospective review of the case histories of all patients who underwent pacemaker implantation in the reference center for a defined population over a 13-year period was undertaken. A li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…He was effectively treated with voriconazole and linezolid. In contrast, Izquierdo et al [ 7 ] described two patients who developed pocket infections secondary to A. fumigatus but almost 1.5 to 2 years after device manipulation. Like Pincus et al, their cases also had risk factors like diabetes, but eventually did well with surgical and medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He was effectively treated with voriconazole and linezolid. In contrast, Izquierdo et al [ 7 ] described two patients who developed pocket infections secondary to A. fumigatus but almost 1.5 to 2 years after device manipulation. Like Pincus et al, their cases also had risk factors like diabetes, but eventually did well with surgical and medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these latter cases were lead infections with a few complicated with endocarditis. Only 5 cases were reported who had a generator pocket infection [ 4 7 ]. Most commonly seen were the Aspergillus species with one case reporting Candida8, but all of them had chronic disease which could have caused the patient to be vulnerable to a fungal infection.…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA), constitute half of all CIED infections caused by S. aureus and are often associated with a worse prognosis [16,17]. The presence of MRSA on patients' skin is an independent risk factor for CIED infection, suggesting that infection may occur during device implantation [11,18]. Culture-negative CIED infections are a particular problem, occurring in approximately 6% to 20% of all CIED infection cases.…”
Section: Medical and Economic-social Significance Of Complications Re...mentioning
confidence: 99%
“…approximately 400 CIED infections), they may have serious consequences for the well-being of patients, and what is more, analyzes included in the INNOWO report showed that the actual cost of treating CIED infection may reach up to PLN 200,000 [38]. On average, treatment procedures for CIED-related infection bring losses of PLN 3,000 to hospitals, and each subsequent day of the patient's hospitalization results in a decline in the financial result center by an average of almost PLN 872 [18]. The INNOWO report emphasized that in the years 2016-2019 there was an increase in the costs of treating infections related to PLN 5.4 million to PLN 7.4 million.…”
Section: Medical and Economic-social Significance Of Complications Re...mentioning
confidence: 99%